Antara Kewajiban Moral dan Beban Sosial: Analisis Praktik Buwuhan Pada Resepsi Pernikahan dalam Perspektif Sosiologi Hukum Islam - Dyana; Isnainingsih; Ramdan Wagianto (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2026)
The practice of buwuhan (offering a contribution or gift) at wedding receptions has long been a part of Indonesian custom, serving as a means to demonstrate solidarity, the spirit of mutual cooperation, and social support for the hosts. However, over time, the meaning of this practice has shifted; it is no longer viewed merely as a voluntary gesture but is often perceived as a moral obligation accompanied by the expectation of a reciprocal return in the future. This study aims to understand the dynamics of buwuhan at wedding receptions from the perspective of Islamic law within a social context, examining the interplay between social norms, religious values, and societal changes. Employing a normative legal approach combined with the sociology of Islamic law, the study relies on literature research. Data were gathered from the Qur'an, Hadith, legislation, and relevant scholarly books and journals, then analyzed using a descriptive-qualitative method. The findings indicate that the practice of buwuhan is fundamentally consistent with the values ​​of mutual assistance (ta'awun) and customary practice ('urf) recognized in Islamic law, provided it is carried out voluntarily and does not conflict with Sharia principles. However, when buwuhan transforms into a burdensome social demand or creates a sense of compulsion, it ceases to align with the Sharia objective of fostering public welfare (maslahah). Therefore, it is essential to re-examine the practice of buwuhan to ensure it continues to strengthen social unity without compromising the values ​​of sincerity and fairness in communal life.